Amphiphilic polyester-b-poly (vinyl amide) copolymers as dual functional kinetic hydrate inhibitors and anti-agglomerants for multiphase flow-assurance - Xiang-Long Ding; Hong-Ju Huang; Yi-Min Dai; Li Wan (Fuel, 2027)

Paternal vitamin D deficiency is associated with offspring testicular developmental abnormalities, fibrosis, and altered sperm miRNA profiles - Yu-Ming Chen; Zhi-Hong Tian; Shi-Yuan Li; Juan Dai; Xing-Ru Wang; Guo-Ying Sun; Min Liu; Berthold Hocher; Mei Tian (Molecular Biology Reports, 2026)

Integrating ex vivo drug sensitivity and genetic mutation analysis improves prediction of chemotherapy response in acute myeloid leukemia - Wěi Li; Min Ji; Wei Li; Ying Zhou; Ruinan Jia; Xin Wen; Shumin Jin; Yiping Hao; Min Dai; Shumei Xu; Qirui Zhou; Huihui Jiang; et al. (Functional & Integrative Genomics, 2026)

Isolation and food-relevant evaluation of a novel lytic Kayfunavirus phage vB-EcoP-B10 for controlling STEC on food-contact surfaces and in raw beef - Yuxin Mu; Min Li; Xiangqi Bai; Qianhong Li; Xiaodong Xia; Ting Zhou; Chunling Zhang; Ying Yu; Yanna Dai; Jifeng Pu; Hu Pan; Xin Wang (Food Research International, 2026)

Synergetic chemical passivation and energy level alignment via multifunctional polyurethane for high-efficiency Sb2S3 solar cells - Yifan Sun; Jiawang Che; Xiaochen Feng; Yanqing Wang; Xiang Li; Zhiping Fang; Min Fan; Dongchen Guo; Hui Dai; Chengwu Shi (Chemical Engineering Journal, 2026)

Recent advances in transition metal-doped MoS2 for advanced oxidation processes: Structural regulation, catalytic mechanisms, and applications - Kaiwen Shi; Liang Dai; Gui Ma; Qianlin Zuo; Min Li; Renbo Wang; Zirong Chen; Xiaosan Song; Bigui Wei; Gang Wang (Journal of Environmental Chemical Engineering, 2026)

Genetically engineered recombinant thrombin R541W-modified bacterial cellulose for rapid hemostasis and wound repair - Ke Zhang; Lei Xiang; Chihao Zhang; Xi Wu; Changming Chen; Lei Li; Min Xin; Xuefeng Wang; Luhan Bao; Jing Dai (Chemical Engineering Journal, 2026)

Spatial distribution and compositional profile of microplastics in oil and gas extraction solid wastes: An overlooked source of microplastics - Yongxu Jin; Jianqi Dai; Xiang Wang; Shan Zhong; Yingzhou Huang; Xudong Mei; Shijie Wang; Min Hao; Jinwei Fang; Yunmin Zeng; Dong Li (Chemical Engineering Journal, 2026)

Superhydrophobic MOFs modified by rosin acid with excellent stability for oil-water separation and catalysis - Siya Guo; Siwei Dai; Junkai Fang; Qingfang Xiong; Yucheng Zhou; Wenting Wang; Min Zhang; Chuntao Kuang; Guoen Yang; Zhaoshuang Li (Journal of Water Process Engineering, 2026)

Spatially distributed modeling of biofilm-induced hydrodynamic evolution in porous media - Hongcheng Zhang; Chaomeng Dai; Jixiang Li; Jiajun Hu; Wang Kai Tong; Jia Jie Zou; Min-tian Gao; Zhi Li; Xihua Wang; Yalei Zhang; Kah Hon Leong; Swee Pin Yeap; et al. (Journal of Hydrology, 2026)

Oat protein-EGCG-sugar beet pectin ternary complexes: Role of pectin in driving non-covalent interactions and improving functional properties - Zihao Chen; Muyao Luo; Taotao Dai; Min Fu; Zhaoying Li; Qin Geng; Jun Chen; Ti Li; Risi Wang (Food Hydrocolloids, 2026)

Multiscale modelling of crystalline swelling-driven triple-pore evolution in bentonite buffer for HLRW disposal - Wen-jie Dai; Yong-gui Chen; Yu-cheng Li; Zhao Sun; Wei-min Ye; Jing-li Xie; Sheng-fei Cao; Zhen-yu Yin (Applied Clay Science, 2026)

A recombinant baculovirus expressing multi-epitopes elicits protective immunity against ALV-J infection in chickens - Yingyi Chen; Yuqin Zheng; Rongmao Chen; Xueqing Li; Wanlin Jiao; Ming Liao; Min Feng; Manman Dai (Veterinary Microbiology, 2026)

Engineering heterostaple in atomically precise palladium cluster for efficient hydrogen peroxide electrosynthesis - Jiachun Li; Yan Sun; Min Du; Shuguang Wang; Baoliang Han; Jiacheng Wang; Xiaoyi Yang; Fangkai Wu; Fuling Liu; Xiaofeng Lei; Afang Dai; Zibao Gan; et al. (Science Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Joule-thermal desert-beetle-inspired mesh for efficient purification of viscous emulsified kitchen oil - Jiawei Sun; Runtang Cai; Xiangyu Huang; Jialuo Dai; Huan Fu; Xinjuan Zeng; Limiao Lin; Penghui Li; Min Zhang (Journal of Water Process Engineering, 2026)

Quality grading of raw goat milk and microbiota-driven quality degradation during storage at 4°C and 10°C - Mengyuan Cao; Min Li; Yizhuo Yan; Yifan Wu; Li Su; Jinghan Dai; Cong Wang; Xin Lv; Yan Zhang; Wupeng Ge; Baowei Yang (International Dairy Journal, 2026)

Benzylisoquinoline alkaloid dimers with antitumor activities from Thalictrum wangii B. Boivin - Qiong Jin; Xue-Meng Liu; Dao-Min Liu; Xiao-Lei Shi; Qiong Yang; Yun-Li Zhao; Li-Xing Zhao; Zhi Dai; Xiao-Dong Luo (Phytochemistry, 2026)

Differential effects of a novel mesoionic insecticide, triflumezopyrim, on Apis mellifera and Apis cerana - Mei-Ling Zhang; Shu-Wei Wang; Wen-Min Li; Sasiprapa Krongdang; Yan-Yan Wu; Ping-Li Dai; Shan-Shan Li; Jing Gao (Journal of Hazardous Materials, 2026)

Multi-thiol grafted PVA/PEI electrospun nanofibers via thiol-ene click chemistry for efficient and selective Au(III) recovery: Experimental and DFT insights - Hongxing He; Ying Xu; Xintao Yang; Peng Li; Enrui Dai; Yi Zhang; Min Li; Linhui Su; Yanjie Zhao; Zhifeng Nie (Desalination, 2026)

Pseudostellaria heterophylla Extract Enhances the Immune Responses in Larimichthys crocea Against Pseudomonas plecoglossicida Infection - Kun Huang Han; Zi Min Li; Li Zhou; Dong Ling Zhang; Ying Li; Zhao Han Sun; Jia Chen; Zhi Deng Lin; Yan Bin Dai; Peng Fei Zou (Fishes, 2026)
Visceral white spot disease caused by Pseudomonas plecoglossicida poses a severe threat to large yellow croaker (Larimichthys crocea) aquaculture. This study investigated the immunomodulatory effects and underlying mechanisms of Pseudostellaria heterophylla extract against P. plecoglossicida infection in L. crocea. Fish were fed a basal diet supplemented with 1% P. heterophylla extract for 30, 45, and 60 days, followed by intraperitoneal injection with 200 μL P. plecoglossicida (1 × 104 CFU/mL). When the control group reached about 50% mortality, transcriptome sequencing of head kidney tissues was performed on the 45 and 60 days post-feeding of the treatment groups to analyze gene expression changes following bacterial infection. Survival rates of the treatment groups were 33.33%, 13.33%, and 20% higher than those of the control group at 30, 45, and 60 days post-feeding, respectively. Transcriptomic analysis revealed time-dependent transcriptional responses: in one group, 45 days post-feeding, 10 differentially expressed genes (DEGs) were identified (2 up-regulated and 8 down-regulated), whereas in another group, 60 days post-feeding, 893 DEGs were detected (417 up-regulated and 476 down-regulated). Functional enrichment analysis (GO, KEGG, and GSEA) demonstrated that DEGs were significantly enriched in immune-related pathways, including Toll-like receptor signaling, chemokine activity, Th1 and Th2 cell differentiation, hematopoietic cell lineage, and cytokine–cytokine receptor interaction. Key immune genes, including chemokines, Toll-like receptors, and T cell regulators, were significantly up-regulated. These findings indicate that P. heterophylla extract enhances both the specific and non-specific immune capabilities of L. crocea in a time-dependent manner, with prolonged supplementation eliciting more robust transcriptional activation of immune defense pathways. This study provides a scientific foundation for developing immunological prevention strategies against P. plecoglossicida infection in aquaculture.

SETD2 governs the regenerative threshold in the liver by gating STAT5-dependent Cox2 signaling - Liping Luo; Ting Chen; Yanzhu Long; Cheng Wang; Peipei Li; Xiaoqi Zhou; Zhengming Du; Tonglang Tang; Jinxuan Wang; Qingliang Zou; Limao Xu; Bo Liu; et al. (Science China Life Sciences, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Regional immunity in the respiratory tract: challenges and opportunities - Shuo Wang; Si Chen; Lianpan Dai; Fengqi Li; Hui Li; Kefang Liu; Xiangzhi Meng; Jian Wang; Hua Yue; Airu Zhu; Bin Cao; Ling Chen; et al. (Science Bulletin, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Inhibition and metabolic toxicity regulation of niacin on Staphylococcus aureus and its application in meat product preservation - Lei Tian; Xiangqi Bai; Chunyang Huang; Min Li; Ting Zhou; Chunling Zhang; Ying Yu; Hu Pan; Yanna Dai; Jifeng Pu; Chengyu Fu; Pengfei Zhang; et al. (International Journal of Food Microbiology, 2026)

Seasonal restructuring of nitrite cycling driven by stratification‐mixing transitions in China's largest estuary - Yangjun Chen; Xianhui S. Wan; Xingzhou Zhang; Peipei Dai; Yuanyuan Yang; Xinwei Li; Minfang Zheng; Min Chen (Limnology and Oceanography, 2026)
Nitrite serves as a key intermediate in the nitrogen cycle, with its microbial‐driven cycling regulated by various environmental factors. However, how nitrite cycling responds to changing environmental conditions remains unclear. Here, we address this question by integrating natural abundance stable isotope techniques with geochemical modeling in China's largest estuary—the Changjiang (Yangtze River) estuary—and its adjacent coastal waters, a dynamic hotspot shaped by strong anthropogenic and natural forces. From summer to autumn, shifts in water column structure—from stratification and hypoxia to mixing and reoxygenation—significantly regulate nitrite dynamics. Nitrite sources exhibit unexpected consistency across seasons, despite oxygen fluctuations from hypoxia to reoxygenation. Conversely, nitrite sinks exhibit clear seasonality and vertical structuring that are closely associated with transitions between stratification and mixing. Active nitrite oxidation is confirmed in the coastal seasonal hypoxic zone, with no clear evidence supporting the occurrence of enzymatic nitrate/nitrite isotopic exchange reaction. These findings advance our understanding of how coastal nitrogen cycling responds to seasonal environmental variability and provide a transferable framework for improving predictions of biogeochemical feedbacks under intensifying stratification and deoxygenation in a changing climate.

Whole-body periodic acceleration: a new countermeasure against bone loss induced by long-term hindlimb unloading - Xuefeng Liu; Jinlong Li; Huijuan Wang; Feng Wu; Hailong Wang; Kaijie Jiang; Min Yuan; Zi Xu; Guanghan Kan; Shujuan Liu; Xiaoqian Dai; Wenjiong Li; et al. (European Journal of Applied Physiology, 2026)

Design and verification of a microbial consortium with an anchoring-interface enhancement strategy for efficient PAHs degradation in groundwater - Wang Kai Tong; Jiajun Hu; Chaomeng Dai; Jia Jie Zou; Han Tang; Piao Yi Jiang; Min-tian Gao; Jixiang Li; Xihua Wang; Yalei Zhang; Ken-Lin Chang; Kah Hon Leong; et al. (Water Research, 2026)

Pomelo peel-graphene aerogel/filter membrane with confocal Raman spectroscopy for rapid separation and identification of microplastics - Zhenqing Dai; Min Chang; Lei He; Yuping Lai; Rijian Mo; Liming Song; Ruikun Sun; Shiqi Jiang; Chengyong Li (Journal of Environmental Chemical Engineering, 2026)

Fe/Cu-γ-Al2O3 catalyst for pilot-scale internal circulation Fenton degradation of methyl orange: performance and mechanism - Dekai Fan; Yanran Lin; Peng Zhu; Yingwen Zhang; Bang Yao; Li Chao; Zhuangzhuang Jia; Jianjun Dai; Yingrui Ning; Rong Xiao; Chen Chen; Lei Gao; et al. (Journal of Environmental Management, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Correction: Morphological and histopathological study of edible bird’s nest on wound healing in mice - Min Li; Bo Liu; Man Yuan; Xiaoli Dai; Shuang Qiu; Xiangkui Zhang; Xiaoyang Zheng; Kai Chen; Chonggang Duan; Daizhou Zhang; Dongliang Wang; Xiangjing Meng (Journal of Molecular Histology, 2026)

Mechanical Behavior and Crack Evolution of Sandstone with Non-connected Double Flaws - Qin Meng; Shunchuan Wu; Feng Dai; Min Ren; Weihua Liu; Jiquan Ma; Fei Li (Geotechnical and Geological Engineering, 2026)

Synergizing root growth and carboxylate release enhance seed yield in maize-soybean intercropping on acidic karst soils - Cheng-Xi Yi; Yi Jin; Long-Gui Li; Yu-Mei Wang; Yu Dai; Qiao Zhu; Xiao-Li Wang; Yinglong Chen; Xiao-Min Wu; Jin He; Sanwei Yang (Field Crops Research, 2026)

A regulatory biomimetic nanoparticle targeting senescent glioma cells for BNCT treatment - Qi Dai; Zhicheng Zhang; Zhiqing Ben; Xiaoyan Sun; Yufan Yang; Yaxin Qin; QiYao Yang; Xiaoyan Bao; Linjie Wu; Ruolin Jiang; Xin Tan; Xufang Ying; et al. (Chemical Engineering Journal, 2026)

Construction of self-sustaining dual regeneration system through co-immobilized multienzyme and cofactor for sustainable 13-hydroxyoctadecadienoic acid synthesis - Xiaoxiao Liu; Kai Li; Pengbo Wang; Kung Wang; Shuhan Dai; Xiaoman Xie; Min Yang; Li Xu; Yunjun Yan; Jinyong Yan (Bioresource Technology, 2026)

A novel bioengineered strategy for efficient heavy metals remediation: Harnessing alkaline phosphatase-displaying E. coli to enhance microbial-induced phosphate precipitation - Zhen Zheng; Xiaoman Xie; Xinyi Hu; Wanlin Zheng; Shuhan Dai; Jianping Liu; Jinyong Yan; Min Yang; Yunjun Yan; Li Xu (Bioresource Technology, 2026)

Halophytes regulate microbial synergy to enhance N removal and mitigate greenhouse gas in low C/N mariculture wastewater: Revealed by isotopic & metagenomics - Zuoliang Sun; Dengpan Dong; Xiefa Song; Yuanrong Wei; Yuanyi Li; Haoyue Dai; Chunmei Liu; Min Zhang; Meng Li (Water Research, 2026)

Impact of glycosylation position on functional characteristics and interaction mechanisms in pea protein-flavonoid complexes: A comparative study of genistein and its O-glycosides - Zihao Chen; Wuzhen Liu; Min Fu; Yuanrui Xu; Jun Chen; Qin Geng; Ti Li; Taotao Dai (Food Hydrocolloids, 2026)

Targeted degradation of emerging pollutants based on specific recognition and ROS confinement effects of molecularly imprinted cavities - Jun Bo Zhang; Xu Jiang; Chaomeng Dai; Jixiang Li; Jiajun Hu; Min-tian Gao; Xueji You; Hongcheng Zhang; Shunyang Li; Peng Qiu; Zhu Zhu; Xihua Wang; et al. (Chemical Engineering Journal, 2026)

Microwave-assisted pyrolysis of dyeing sludge: Reaction kinetics, elemental transformation, and heavy metal migration - Dekai Fan; Rong Xiao; Wahab Nasarul; Chunbao Zhou; Yingwen Zhang; Bang Yao; Li Chao; Jianjun Dai; Gul Urooj; Yingrui Ning; Peng Zhu; Chen Chen; et al. (Chemical Engineering Journal, 2026)

Winter oilseed rape-quinoa rotation and humic acid mitigate continuous cropping obstacles by reshaping rhizosphere microbial communities and root exudate profiles - Dai Jing; Lv Huimin; Jiang Zhijun; Zhang Weibin; Chen Jei; Ding Pengcheng; Wu Xiangyun; Gao Zhiqiang; Li Lina; Sun Min; Ren Aixia (Plant and Soil, 2026)

Efficient degradation and deep defluorination mechanism of perfluorooctanoic acid via sulfur-modified nanoscale zero-valent iron activation of peroxymonosulfate - Liang Dai; Mengjie Zhang; Yibing Ma; Gui Ma; Qianlin Zuo; Min Li; Renbo Wang; Kaiwen Shi; Bigui Wei; Gang Wang (Journal of Water Process Engineering, 2026)

miR-133b-3p Mitigates D-Galactose-Induced Hippocampal Neuron Aging Through Autophagy Regulation via the MAPK/ERK Signaling Pathway - Yang Cao; Chen Zhao; Jiaxin Li; Qiang Gao; Chunmei Lv; Jiao Wang; Na Qiang; Wenwen Zhang; Huiyu Su; Xinyu Min; Jinfeng Liu; Xiaoqi Dai; et al. (Molecular Neurobiology, 2026)

Comparative study on organic composts in blueberry: insights into soil physicochemical properties and heavy metal control - Hao Tang; Ying Dai; Lijuan Tang; Juan Guo; Ke Wen; Fangke Yuan; Lin Li; Yuan Jin; Jinlu Li; Min Xiao; Heng Xu (Environmental Geochemistry and Health, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Toward satisfactory public accessibility: A crowdsourcing approach through online reviews to inclusive urban design - Lingyao Li; Songhua Hu; Yinpei Dai; Min Deng; Parisa Momeni; Gabriel Laverghetta; Lizhou Fan; Zihui Ma; Xi Wang; Siyuan Ma; Jay Ligatti; Libby Hemphill (Computers, Environment and Urban Systems, 2025)

Fungal mycelial pellet as a biosponge for bacterial immobilization: A novel biocarrier for synergistic adsorption-degradation of PAHs - Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Wang Kai Tong; Hong Cheng Zhang; Min-tian Gao; Yalei Zhang; Zhi Li; Kah Hon Leong; Lang Zhou; Ken-Lin Chang; Swee Pin Yeap (Chemical Engineering Journal, 2025)

Engineering Escherichia coli nissle 1917 with lactonase ZHD101 alleviates zearalenone-induced intestinal disruption and reproductive toxicity in rat - Min Dai; Siyuan Liu; Renming Cai; Deqiang Li; Yijiao Wen; Jingwen Jiang; Na Hao; Qin Wang; Xiaowei Gao (World Journal of Microbiology and Biotechnology, 2025)

Partially empirical model-based water depth retrieval in shallow sea using GF5-AHSI hyperspectral remote sensing data: a case study on Meizhou Bay in Fujian Province, China - Xiaoai Dai; Yunfeng Shan; Cheng Li; Hao Chen; Tangrui Dai; Ge Qu; Tianyi Xie; Chengbo Tong; Htun Naing; Min Zhang (Frontiers of Earth Science, 2025)

Predictive biomarkers for valproic acid-induced hepatotoxicity in Chinese patients with epilepsy: the role of metabolites and genetic polymorphisms - Dingsheng Wen; Zhuojia Chen; Ziyi Chen; Xue Bai; Hongliang Li; Juan Chen; Qiling Dai; Guoping Zhong; Jiaming Qin; Guanzhong Ni; Min Huang; Liemin Zhou; et al. (Food and Chemical Toxicology, 2025)

Co-nZVI@ATP activated persulfate for the degradation of Bisphenol S: Treatment efficiency and mechanism - Zhenle Lei; Juan Ma; Yujie Cao; Mengjie Zhang; Qianlin Zuo; Min li; Yuxue Liu; Peng Wan; Liang Dai (Environmental Research, 2025)

Sequential targeted nanomedicine MPC treats cerebral ischemia-reperfusion injury via neuronal microenvironment reprogramming - Shuya Wang; Ruishi Li; Xiaojing Shi; Tingli Xiong; Wenxuan Zheng; Weimin Qi; Min Liu; Lin Dai; Qian Lin; Rui Huang; Wei Dai; Min Zhou; et al. (Chemical Engineering Journal, 2025)

A Product-based Life-cycle Integration Platform for sustainable plastic bottles from agricultural biowaste - Yibo Zhang; Min Dai; Bin Chen; Hongyi Xie; Zhiwei Li; Yutao Wang (Chemical Engineering Journal, 2025)

Efficient activation of percarbonate by metal-free carbonylated activated carbon for green groundwater remediation: Performance, mechanism, applicability, and environmental implications - Jun Bo Zhang; Yi Yang; Chaomeng Dai; Jixiang Li; Yucang Liang; Jiajun Hu; Min-tian Gao; Xueji You; Xu Jiang; Shunyang Li; Xihua Wang; Zhi Li; et al. (Journal of Hazardous Materials, 2025)

Immobilization of simulated An and An in radioactive sludge via microwave sintering: Mechanism and properties - Gaiyuan Chen; Yong Liu; Zhengxin Wu; Xingwang Dai; ChengYan Yan; Yourui Jiang; Min Chen; Jiawei Li (Journal of Environmental Chemical Engineering, 2025)

Geochronology and geochemistry of the Shengtieling REE-Fe deposit in the Jiao-Liao-Ji belt, North China Craton: Implications for hydrothermal mineralization related to the ∼1.85 Ga tectono-magmatic event - Xiao-Hui Wang; Yu-Bo Ma; Li-Xing Li; Hou-Min Li; Yi Wang; Yang Dai; Xuan Wu (Journal of Asian Earth Sciences, 2025)

Myxomycetes in urban green space in subtropical China: Spatiotemporal patterns override forest type effects - Wen-Long Song; Di Lin; Min-Li Cai; Xia Chen; Qun Dai; Shuang-Lin Chen (Fungal Biology, 2025)

Photo-self-Fenton system driven by ultrasmall Fe nanoparticles induced internal electric field toward efficient wastewater purification - Zhihui Yin; Min Dai; Shuaiqi Zhang; Chengzhen Meng; Yaru Li; Fengming Situ; Kena Qin; Chun Hu; Fan Li (Environmental Research, 2025)

A caries band-aid: Sequential anti-biofilm and remineralization therapy for functional and aesthetic restoration of enamel caries - Yingming Yang; Min Zhang; Ziyou Wang; Hanxiao Chen; Qinyue Dai; Jiaojiao Yang; Jianshu Li; Jiyao Li; Siying Tao (Chemical Engineering Journal, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Morphological and histopathological study of edible bird’s nest on wound healing in mice - Min Li; Bo Liu; Man Yuan; Xiaoli Dai; Shuang Qiu; Xiangkui Zhang; Xiaoyang Zheng; Kai Chen; Chonggang Duan; Daizhou Zhang; Dongliang Wang; Xiangjing Meng (Journal of Molecular Histology, 2025)

MAO-A inhibition alleviates sepsis-driven lung injury via Nrf2/HO-1 pathway activation and suppression of pyroptosis - Min Li; Hu Li; Liming Gong; Xinmin Chen; Jincan Dai; Jirong Tian; Xiaochuan Yin; Qinghe Yu (Journal of Molecular Histology, 2025)

Recessive variants in TWNK cause syndromic and non-syndromic post-synaptic auditory neuropathy through MtDNA replication defects - Xue Gao; Ying Ma; Wei-Qian Wang; Guo-Jian Wang; Kun Yang; Jin-Cao Xu; Sha-Sha Huang; Xiang Wang; Li-Min Hu; Xi Wang; Qiu-Quan Wang; Zhen-Dong Wang; et al. (Human Genetics, 2025)

Discovery and Significance of Paleozoic Granite Porphyry in the Haidewula Uranium Deposit, East Kunlun Orogenic Belt, Northwest China - Jian-Hua Duan; Tong Liu; Jia-Wen Dai; Hui-Min Su; Yan-Qiang Li; Shao-Yong Jiang (Journal of Earth Science, 2025)

Tailoring lignocellulose-derived biochar for peroxymonosulfate-based catalytic environments: Optimizing active sites, revealing activation mechanisms, and advancing groundwater remediation applications - Jun Bo Zhang; Chaomeng Dai; Jiajun Hu; Jixiang Li; Min-tian Gao; Yeap Swee Pin; Kah Hon Leong; Ken-Lin Chang; Xing Song Xu; Xu Jiang (Journal of Hazardous Materials, 2025)

Harnessing CO2 for sustainable bioelectricity: An engineered two-stage microbial co-culture approach with enhanced acetate metabolism - Xiaoman Xie; Ying Wu; Yiran Lv; Shuhan Dai; Huanhuan Li; Li Xu; Min Yang; Jinyong Yan; Yunjun Yan (Bioresource Technology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Scandium and gallium in weathered basalts as unconventional resources - Mei-Fu Zhou; Wen Winston Zhao; Zhenchao Wang; Min Wang; Shengbiao Yang; Lei Meng; Liang Qi; Guangfu Xing; Xiang Li; Dai Zhou (Journal of Asian Earth Sciences, 2025)

Glucose protects the pacific white shrimp Litopenaeus vannamei against Vibrio alginolyticus by inhibiting biofilm formation - Weibo Shi; Fa Dai; Ya Li; Zihao Sun; Min Meng; Qiuyan Yang; Weiwei Zhang (Fish & Shellfish Immunology, 2025)

Modelling the crystalline swelling process of montmorillonite incorporating boundary effects - Wen-jie Dai; Yong-gui Chen; Yu-cheng Li; Wei-min Ye; Qiong Wang (Computers and Geotechnics, 2025)

Ore-forming fluid for the formation of banded iron formation-hosted high-grade magnetite ores of the North China Craton: Constraints from pyrite trace elements and sulfur isotopes - Yi Wang; Li-Xing Li; Hou-Min Li; Jian-Fei Fu; Yang Dai; Xiao-Hui Wang; Xuan Wu (Journal of Asian Earth Sciences, 2025)

Effects of Microclimates on Species Richness of Epiphytic and Non‐Epiphytic Bryophytes Along a Subtropical Elevational Gradient in China - Zun Dai; Hong‐Wei Zhang; Hong Qian; Min Li; Rui‐Ping Shi; Zhao‐Chen Zhang; Jian Zhang; Hong‐Qing Li; Jian Wang (Journal of Biogeography, 2025)
Aim Biodiversity patterns along elevational gradients have been well documented for vascular plants and terrestrial vertebrates, but we know relatively little about the elevational patterns of bryophytes and their underlying mechanisms, especially the effect of forest microclimate on epiphytic and non‐epiphytic bryophytes. Here we study the influence of microclimates on the richness of epiphytic and non‐epiphytic bryophytes as a whole, and for liverworts and mosses separately, in forests along an elevational gradient ranging from 369 to 1476 m in a subtropical region. Location Mt. Tianmu in eastern China. Methods We sampled bryophytes in each of 16 vegetation plots, each of the size of 20 by 20 m, along the elevational gradient and distinguished between mosses and liverworts and between epiphytic and non‐epiphytic species. We measured climate conditions at local sites. Species richness of bryophytes along the elevational gradient was related to six microclimate variables, using correlation and regression analyses and a variation partitioning approach. Results Overall, species richness of bryophytes showed a slightly decreasing trend with elevation, and epiphytic and non‐epiphytic bryophyte richness showed different elevational patterns. Compared to non‐epiphytic bryophytes, species richness of epiphytic bryophytes was more influenced by air microclimate. We also found that species richness of bryophytes was influenced by both microclimate extreme variables and microclimate seasonality variables. In sum, utilising in situ air and soil microclimatic monitoring data, our study offers a more accurate assessment of the relationship between bryophyte species richness and their habitats. Main Conclusions Our results highlight the importance of considering the ecological differences between mosses and liverworts, and distinguishing between microhabitats of sampled bryophyte assemblages when exploring the patterns and drivers of bryophyte diversity along elevational gradients.

Efficient degradation of dodecyl dimethyl benzyl ammonium chloride by activated carbon-loaded nanoscale zero-valent iron activated persulfate - Min Li; Yibing Ma; Gui Ma; Mengjie Zhang; Qianlin Zuo; Gang Wang; Jun Ren; Tiaobin Zhao; Liang Dai (Journal of Water Process Engineering, 2025)

Synergistic effects of bimetallic Co, Cu activity sites and heteroatom-doped carbon nanotube-entangled phosphide for high capacity lithium storage - Hanlin Shen; Zhuo Li; Min Dai; Yunan Tian; Zhaoshun Liu; Zhonghao Zhou; Zhi Li; Xianwei Hu (Chemical Engineering Journal, 2025)

NEFL Modulates NRN1-Mediated Mitochondrial Pathway to Promote Diacetylmorphine-Induced Neuronal Apoptosis - Sensen Zhu; Liping Su; Mengjie Zhuang; Li Liu; Min Ji; Jingyu Liu; Chenlu Dai; Jinling Xiao; Yaling Guan; Long Yang; Hongwei Pu (Molecular Neurobiology, 2025)

Protective effects of resveratrol on honeybee health: Mitigating pesticide-induced oxidative stress and enhancing detoxification - Linlin Liu; Min Shi; Yanyan Wu; Jiali Hao; Junxiu Guo; Shanshan Li; Pingli Dai; Jing Gao (Pesticide Biochemistry and Physiology, 2025)

Interface selectivity-based biochar: Directional evolution of properties, application & carbon neutralization evaluation - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Mei Ru Yue; Yun Dong Liu; Bu Li; Jia Jie Zou; Jia Wang; Han Tang; Min-tian Gao; Yucang Liang; Wenjuan Wang; et al. (Chemical Engineering Journal, 2025)

3D printed emulsion gels stabilized by whey protein isolate/polysaccharide as sustained-release delivery systems of β-carotene - Lei Feng; Ming Li; Zhuqing Dai; Yayuan Xu; Zhongyuan Zhang; Min Zhang; Dongxing Yu; Dajing Li (Carbohydrate Polymers, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Cathode-mediated electrochemical conversion of phenol to benzoquinone in wastewater: High yield rate and low energy consumption - Zonglin Li; Zhiyuan Feng; Min Chen; Yankai Song; Yicen Dai; Shun Mao; Hongying Zhao (Water Research, 2025)

Effects of synthetic microbial community fermentation on volatile flavor and quality characteristics of ginger pickle - Yankai Min; Qing Zhang; Jiali Liu; Yanling Shang; Yilin Hou; Min Zhang; Jingwen Dai; Ziyu Li; Wenliang Xiang; Jie Tang (Food Research International, 2025)

Bifunctional nanobody facilitates a colorimetric and fluorescent dual-mode immunoassay of Staphylococcal enterotoxin A - Yao Zhang; Di Liu; Yudong Tian; Min Li; Yuhuan Li; Ting Zhou; Qin Zhao; Min Zhang; Ying Yu; Hu Pan; Yanna Dai; Zhuoma Dawa; et al. (Food Chemistry, 2025)

Tracking the geographical distribution of the Asian citrus psyllid Diaphorina citri throughout China using mitogenomes and endosymbionts - Fengnian Wu; Zehan Dai; Min Shi; Jianjian Huang; Hui Zhu; Yuzhong Zheng; Zikai Chen; Xiuhong Li; Xiaoling Deng; Eduardo G. P. Fox (Journal of Pest Science, 2025)

Fluorescent biosensor for lead ion detection based on GR-5 DNAzyme and self-hybridization chain reaction - Min Li; Huanxi Chen; Yu Zhang; Yuxin Cheng; Fengyi Lin; Haibo Wang; Jianyuan Dai (Analytica Chimica Acta, 2025)

A self-sustainable DNA amplification circuit for sensitive microRNA imaging - Chuanyi Liu; Ziling Huang; Zhigang Li; Xiaojiao Dai; Qingmin Chen; Min Chen; Yi Xu; Xiaomei Chen; Fuan Wang; Quansheng Chen; Jie Wei (Analytica Chimica Acta, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Characterization of pea protein-different types of glycoside flavonoid complex interactions and functional properties - Zihao Chen; Min Fu; Jun Chen; Guowen Zhang; Qin Geng; Xing Hu; Yihui Wang; Ti Li; Ruihong Liang; Taotao Dai (Food Research International, 2025)

Multiscale volumetric deformation in compacted bentonite triggered by anisotropic crystalline swelling - Wen-jie Dai; Yong-gui Chen; Yu-cheng Li; Wei-min Ye; Qiong Wang; Zhen-yu Yin (Engineering Geology, 2025)

Design, synthesis and herbicidal activity of novel cyclohexanedione derivations containing pyrazole and pyridine groups as potential HPPD inhibitors - Shuai-Tao Hou; Ling Han; Wen-Rui Li; Guang-Yu Dai; Yu Liu; Ai-Min Lu; Chun-Long Yang; Min Chen (Molecular Diversity, 2025)

Protective effect of Apelin-13 on oxygen and glucose deprivation induced-damage in retinal ganglion cells cultured in vitro - Li Dai; Linlin Luo; Ya Zhang; Min Fu; Ling Yu (Journal of Molecular Histology, 2025)

Development and mechanistic study of phosphate tailings based soil heavy metal prophylactic agents with encapsulated structure for lead stabilization and phosphorus speciation in soils - Luming Dai; Jiahao Li; Jiaxing Zhang; Xuli Li; Tong Liu; Qinqin Yu; Shaoyang Tao; Min Zhou; Haobo Hou (Journal of Environmental Management, 2025)

Glycated walnut meal peptide‑calcium chelates (COS-MMGGED-Ca): Preparation, characterization, and calcium absorption-promoting - Zilin Wang; Litong Liu; Haifen Jiang; Lingfei Li; Min Yang; Jiahe Dai; Liang Tao; Jun Sheng; Yang Tian (Food Chemistry, 2025)

A tetrahedral DNA nanoplatform with ultrasound-triggered biomimetic nanocarriers for targeted siMCM2 delivery and reversal of imatinib resistance in gastrointestinal stromal tumors - Li Han; Quan Dai; Chuanshi He; Jinshun Xu; Likun Cui; Xiaoxiao Xie; Zijian Zhang; Min Zhuang; Xiangyu Li; Man Lu (Chemical Engineering Journal, 2025)

Highly Efficient Oxidation of N, N-Dimethylformamide at Low Temperature over a Mn-based Catalyst by Optimization Support - Dongsheng Ye; Min Ding; Meixingzi Gao; Mingqi Li; Yu Wang; Lai Jin; Wangcheng Zhan; Li Wang; Yun Guo; Qiguang Dai; Yanglong Guo; Aiyong Wang (Chemical Engineering Journal, 2025)

A Review of Iron-Based Catalysts for Persulfate Activation to Remove PFAS in Water: Catalytic Effects of Various Iron Species, Influencing Factors and Reaction Pathways - Mengjie Zhang; YiYi Li; Xia Tian; Liang Dai; Gang Wang; Zhenle Lei; Gui Ma; Qianlin Zuo; Min Li; Mengmeng Zhao; Jun Ren (Water, Air, & Soil Pollution, 2025)

The Pb capture mechanism of soil prophylactic agents prepared from phosphorus tailings and the influence of phosphorus speciation on its slow-release mechanism - Luming Dai; Jiahao Li; Jiaxing Zhang; Xuli Li; Tong Liu; Qinqin Yu; Shaoyang Tao; Min Zhou; Haobo Hou (Science of The Total Environment, 2024)

Conjugated diamine cation based halide perovskitoid enables robust stability and high photodetector performance - Xin Yang; Xu-Dong Wang; Wen-Guang Li; Yu-Hua Huang; Ling-Bin Wang; Jia-Min Liu; Long Jiang; Dai-Bin Kuang (Science Bulletin, 2024)

ent-Kaurane diterpenoids from Isodon henryi and their anti-inflammatory activities - Yi-xiao Li; Jun Chi; Ling-xia Zhang; Fang Wang; Wei-jin Zhang; Zhi-min Wang; Li-ping Dai (Phytochemistry, 2024)

Eco-friendly, stable, and high-performance biochar prepared by a twice-modification scheme: Saccharification of raw materials & thermal air oxidation of biochar - Yundong Liu; Bu Li; Wang Kai Tong; Han Tang; Zhaoli Ping; Wenjuan Wang; Min-tian Gao; Chaomeng Dai; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Management, 2024)

Effects of cellulase treatment on properties of lignocellulose-based biochar - Bu Li; Yundong Liu; Wang Kai Tong; Jun Bo Zhang; Han Tang; Wenjuan Wang; Min-tian Gao; Chaomeng Dai; Nan Liu; Jiajun Hu; Jixiang Li (Bioresource Technology, 2024)

Melatonin Ameliorates Abnormal Sleep-Wake Behavior via Facilitating Lipid Metabolism in a Zebrafish Model of Parkinson’s Disease - Meng-Zhu Pang; Han-Xing Li; Xue-Qin Dai; Xiao-Bo Wang; Jun-Yi Liu; Yun Shen; Xing Xu; Zhao-Min Zhong; Han Wang; Chun-Feng Liu; Fen Wang (Neuroscience Bulletin, 2024)

Biodegradable MAM-based amphiphilic block copolymers: Toward efficient and eco-friendly kinetic inhibitors for methane hydrate formation - Li Wan; Xiang-Long Ding; Ai-Xiang Liu; Hao Cui; Jin-Rong Zhong; Yi-Min Dai (Chemical Engineering Journal, 2024)

Highly efficient Ru/CeO2 catalyst using colloidal chemical method for propane oxidation - Jiaorong Yan; Yunyun Wang; Min Ding; Xiang Zheng; Li Wang; Yun Guo; Yanglong Guo; Qiguang Dai; Wangcheng Zhan; Aiyong Wang (Chemical Engineering Journal, 2024)

In situ surface-enhanced Raman spectroscopy for the detection of nanoplastics: A novel approach inspired by the aging of nanoplastics - Xiaoxin Huang; Jinchan Huang; Meilin Lu; Yu Liu; Guangzheng Jiang; Min Chang; Wenhui Xu; Zhenqing Dai; Chunxia Zhou; Pengzhi Hong; Chengyong Li (Science of The Total Environment, 2024)

Understanding the benefits and challenges of harvested wood products in response to climate change - Meili Xue; Min Dai; Huaqing Li; Huijing Deng; Sijing Wang; Mingxing Sun; Yutao Wang (Resources, Conservation and Recycling, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Fluorinated ionic liquid mediated nanostructure with enhanced conductivity and fluorine retention in Na3V2(PO4)2F3 cathode toward high-performance sodium-ion batteries - Yang Yan; Jun-Qing Xu; Jun-Ming Cao; Han-Wei Huang; Sen-Sen Xue; Guang-Lan Li; An-Min Liu; Cheng-Jie Li; Dongmei Dai; Bao Li; Xing-Long Wu (Chemical Engineering Journal, 2024)

A novel iron oxide (Fe3O4)-laden titanium carbide (Ti3C2) MXene stacks for the efficient removal of tetracycline from aqueous solution - Xinyu Hu; Guizhen Li; Yao Zhang; Mingrong Lu; Wei Pu; Yansu Dai; Min Yang; Hongbin Wang (Chemosphere, 2024)

Prevalence and molecular characteristics of intestinal pathogenic Escherichia coli isolated from diarrheal pigs in Southern China - Qian Li; Jing-Jing Dai; Shu-Yi Chen; Ruan-Yang Sun; Dong Wang; Shuan-Cheng Bai; Min-Ge Wang; Jian Sun; Xiao-Ping Liao; Ya-Hong Liu; Liang-Xing Fang (Veterinary Microbiology, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Phosphorus-based soil prophylactics for managing Pb contamination in soil: Slow-release kinetics and microbiological effects - Luming Dai; Jiahao Li; Jiaxing Zhang; Qingyuan Zeng; Tong Liu; Qinqin Yu; Shaoyang Tao; Min Zhou; Haobo Hou (Science of The Total Environment, 2024)

Activated carbon/persulfate-driven in-situ remediation of naphthalene-polluted groundwater: Insights into active sites, passivation-activation mechanisms and practical applications - Chaomeng Dai; Jun Bo Zhang; Jia Jie Zou; Jiajun Hu; Min-tian Gao; Zhi Li; Yucang Liang; Lang Zhou (Journal of Environmental Chemical Engineering, 2024)

Efficacy and safety of dabigatran and rivaroxaban in atrial fibrillation patients with impaired liver function: a multicenter retrospective cohort study - Xinhai Huang; Wenlin Xu; Guilan Wu; Ruijuan Li; Ping Gu; Qiaowei Zheng; Xiumei Liu; Hengfen Dai; Xiangsheng Lin; Yuxin Liu; Xiaoming Du; Jun Su; et al. (European Journal of Clinical Pharmacology, 2024)

Multiple stresses induced by chronic exposure to flupyradifurone affect honey bee physiological states - Jin Chen; Yong-Jun Liu; Qiang Wang; Li Zhang; Sa Yang; Wang-Jiang Feng; Min Shi; Jing Gao; Ping-Li Dai; Yan-Yan Wu (Science of The Total Environment, 2024)

High sensitivity in quantitative analysis of mixed-size polystyrene micro/nanoplastics in one step - Wenhui Xu; Zhenqing Dai; Xiaoxin Huang; Guangzheng Jiang; Min Chang; Chenying Wang; Tingting Lai; Huanming Liu; Ruikun Sun; Chengyong Li (Science of The Total Environment, 2024)

CO2 mineralization and utilization by tailings sand in China for potential carbon sinks and spatial project layout - Huaqing Li; Yahui Bian; Mingliang Liu; Jianyi Lin; Min Dai; Hongyi Xie; Huajun Yu; Bin Chen; Meili Xue; Zhiwei Li; Jingjing Yin; Liming Xue (Resources, Conservation and Recycling, 2024)

Nanobubbles improve peroxymonosulfate-based advanced oxidation: High efficiency, low toxicity/cost, and novel collaborative mechanism - Jun Bo Zhang; Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Xueji You; Min-tian Gao; Jixiang Li; Rongbing Fu; Yalei Zhang; Kah Hon Leong; Xing Song Xu (Journal of Hazardous Materials, 2024)

A macroscopic model for predicating stepwise crystalline swelling of montmorillonite - Wen-jie Dai; Yong-gui Chen; Yu-cheng Li; Wei-min Ye; Qiong Wang (Computers and Geotechnics, 2024)

Rice rhizospheric effects and mechanism on soil cadmium bioavailability during silicon application - Yi Yang; Hua Peng; Kai Deng; Yu Shi; Wei Wei; Saihua Liu; Changjun Li; Jian Zhu; Yanjiao Dai; Min Song; Xionghui Ji (Science of The Total Environment, 2024)

Overall and geographic pattern of incidence, fatality and mortality of sepsis among hospitalized non-child cancer patients in China: A nationwide cross-sectional study - Bin Lu; Yang Xu; Na Li; Yueyang Zhou; Xudong Ma; Yan Chen; Run Dong; Xiang Zhou; Min Dai; Hongda Chen; Li Weng; Bin Du (Science Bulletin, 2024)

Joint effects of green space and air pollutant exposure on preterm birth: evidence from a nationwide study in China - Tan Mi; Zhimei Qiu; Chunyuan Li; Wenyan Li; Yuyang Gao; Zhiyu Chen; Wenli Xu; Zhen Liu; Qi Li; Min Jiang; Hanmin Liu; Li Dai; et al. (Environmental Science and Pollution Research, 2024)

Characteristics of typical intermediate and semi volatile organic compounds in Shanghai during China International Import Expo event - Taikui An; Yingjie Li; Rui Wang; Sheng'ao Jing; Yaqin Gao; Shuyu Liu; Dandan Huang; Min Zhou; Haixia Dai; Cheng Huang; Jun Lu; Hongli Wang; et al. (Chemosphere, 2024)

Antihypertensive treatment during pregnancy induces long-term changes in gut microbiota and the behaviors of the attention deficit hyperactivity disorder offspring - Hong-Bao Li; Meng-Lu Xu; Wen-Jie Xia; Yuan-Yuan Dong; Bo Peng; Qing Su; Xiao-Min Wang; Jia-Yue Yu; Ya-Nan Gao; Jun-Zhe Wu; Meng-Yue Xu; Jin-Bao Yang; et al. (Toxicology and Applied Pharmacology, 2024)

Straw management adopted by large farms sustains grain yield but mitigates greenhouse gas emissions - Zhenzhen Li; Yong Lin; Zheng-Rong Kan; Sana ur Rehman; Atta Mohi Ud Din; Feng-Min Li; Shixiang Zhang; Ping Wu; Yingfu Ding; Chensheng Xu; Congying Rao; Huaxin Dai; et al. (Field Crops Research, 2024)

Testing for adaptive changes linked to range expansion following a single introduction of the fall webworm - Jin‐Xu Dai; Li‐Jun Cao; Jin‐Cui Chen; Fangyuan Yang; Xiu‐Jing Shen; Li‐Jun Ma; Ary Anthony Hoffmann; Min Chen; Shu‐Jun Wei (Molecular Ecology, 2024)
Adaptive evolution following colonization can affect the impact of invasive species. The fall webworm (FWW) invaded China 40 years ago through a single introduction event involving a severe bottleneck and subsequently diverged into two genetic groups. The well‐recorded invasion history of FWW, coupled with a clear pattern of genetic divergence, provides an opportunity to investigate whether there is any sign of adaptive evolution following the invasion. Based on genome‐wide SNPs, we identified genetically separated western and eastern groups of FWW and correlated spatial variation in SNPs with geographical and climatic factors. Geographical factors explained a similar proportion of the genetic variation across all populations compared with climatic factors. However, when the two population groups were analysed separately, environmental factors explained more variation than geographical factors. SNP outliers in populations of the western group had relatively stronger response to precipitation than temperature‐related variables. Functional annotation of SNP outliers identified genes associated with insect cuticle protein potentially related to desiccation adaptation in the western group and genes associated with lipase biosynthesis potentially related to temperature adaptation in the eastern group. Our study suggests that invasive species may maintain the evolutionary potential to adapt to heterogeneous environments despite a single invasion event. The molecular data suggest that quantitative trait comparisons across environments would be worthwhile.

Thalassinoides ichnofabrics from the Zhangxia Formation (Cambiran Miaolingian series) in Henan province: Bioturbators as Ecosystem engineers - Bingchen Liu; Yong'an Qi; Min Wang; Wenyi He; Yaogang Du; Da Li; Mingyue Dai (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Tsaokoflavanols A1–J1: Flavanol-fatty alcohol hybrids with HPL inhibitory activity from Amomum tsao-ko - Tian-Rong Yang; Shi-Chao Huang; Yun-Fen Wang; Zai-Xiang Lou; Shao-Xing Dai; Li-Hua Su; Min Xu (Phytochemistry, 2024)

Interactive effects of dinotefuran and Nosema ceranae on the survival status and gut microbial community of honey bees - Linlin Liu; Min Shi; Yanyan Wu; Xianbing Xie; Shanshan Li; Pingli Dai; Jing Gao (Pesticide Biochemistry and Physiology, 2024)

Formation and prolonged preservation of dense arc root cumulates: insights from retrograded eclogite xenoliths in the western Yangtze craton - Min Wang; Jian-Ping Zheng; Hong-Kun Dai; Qing Xiong; Yi-Xiong Li; Jin-Wei Guo (Contributions to Mineralogy and Petrology, 2024)

Eco-friendly and stable triclosan removal from groundwater using peroxyacetic acid activated with biochar produced from saccharification residues - Wang Kai Tong; Chaomeng Dai; Chenyan Jia; Jiajun Hu; Min-tian Gao; Jixiang Li; Jun Bo Zhang; Han Tang; Yucang Liang; Wei Teng; Zhi Li; Shuguang Liu; et al. (Chemical Engineering Journal, 2024)

Laccase-evoked removal of antibiotics: Reaction kinetics, conversion mechanisms, and ecotoxicity assessment - Kai Sun; Mei-Hua Chen; Xue-Min Qi; Dan Hong; Ling-Zhi Dai; Shun-Yao Li; Yi-Chen Lu; Han-Qing Yu (Critical Reviews in Environmental Science and Technology, 2024)

A novel eco-friendly strategy for removing phenanthrene from groundwater: Synergism of nanobubbles and rhamnolipid - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Jixiang Li; Min-tian Gao; Xueji You; Xin Ru Feng; Zhi Li; Lang Zhou; Yalei Zhang; Xiaoying Lai; Long Kahon; et al. (Science of The Total Environment, 2024)

Phosphate tailings-based slow-release heavy metal passivation materials: Mechanism, environmental risk, and microbial community evolution - Jiaxing Zhang; Luming Dai; Jiahao Li; Qingyuan Zeng; Min Zhou; Haobo Hou (Journal of Cleaner Production, 2024)

Metabolic engineering of Paenibacillus polymyxa for effective production of 2,3-butanediol from poplar hydrolysate - Jikun Zhang; Jianzhi Zhao; Quanbin Fu; Haiyang Liu; Min Li; Zhongyue Wang; Wei Gu; Xueming Zhu; Rongshan Lin; Li Dai; Kai Liu; Chengqiang Wang (Bioresource Technology, 2024)

Investigation on toxicity and mechanism to Daphnia magna for 14 disinfection by-products: Enzyme activity and molecular docking - Jin J. Li; Min J. Dai; Jun Z. Xue (Science of The Total Environment, 2023)

Shumkonia mesophila gen. nov., sp. nov., a novel representative of Shumkoniaceae fam. nov. and its potentials for extracellular polymeric substances formation and sulfur metabolism revealed by genomic analysis - Min Yang; Xue Zhang; Shichun Ma; Qiumei Zhang; Chenghui Peng; Hui Fan; Lirong Dai; Jiang Li; Lei Cheng (Antonie van Leeuwenhoek, 2023)

Overcoming the fluorescent interference during Raman spectroscopy detection of microplastics - Yu Liu; Jiale Hu; Liqian Lin; Bing Yang; Minhua Huang; Min Chang; Xiaoxin Huang; Zhenqing Dai; Shengli Sun; Lei Ren; Chengyong Li (Science of The Total Environment, 2023)

Interaction and binding mechanism of cyanidin-3-O-glucoside to lysozyme in varying pH conditions: Multi-spectroscopic, molecular docking and molecular dynamics simulation approaches - Hailong Gui; Qiao Jiang; Jinlong Tian; Zang Zhihuan; Shufang Yang; Yiyun Yang; Meili Xin; Min Zhao; Jian Dai; Bin Li (Food Chemistry, 2023)

Test of the colonization ability of the invasive alien plant Flaveria bidentis (Asteraceae) in southern China - Li Xin-Chen; Chen Xi; Dong Xue-jing; Wang Lai-Le; Yi-chen Li; Shi Zhi-Hua; Song Xiao-ling; Qiang Sheng; Dai Wei-min; Wei-Min Dai (Biological Invasions, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Auxiliary Diagnosis of Papillary Thyroid Carcinoma Based on Spectral Phenotype - Bailiang Zhao; Yan Wang; Menghan Hu; Yue Wu; Jiannan Liu; Qingli Li; Min Dai; Wendell Q. Sun; Guangtao Zhai (Phenomics, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Cryo-EM structure and rational engineering of a superefficient ochratoxin A-detoxifying amidohydrolase - Longhai Dai; Du Niu; Jian-Wen Huang; Xian Li; Panpan Shen; Hao Li; Zhenzhen Xie; Jian Min; Yumei Hu; Yu Yang; Rey-Ting Guo; Chun-Chi Chen (Journal of Hazardous Materials, 2023)

Effects of functional group loss on biochar activated persulfate in-situ remediation of phenol pollution in groundwater and its countermeasures - Chaomeng Dai; Jun Bo Zhang; Min-tian Gao; Yalei Zhang; Jixiang Li; Jiajun Hu (Journal of Environmental Management, 2023)

A new idea for efficient copper recovery from wastewater by electrodeposition: Adsorption pretreatment - Shuai Li; Min Dai; Imran Ali; Hengzhi Bian; Changsheng Peng (Desalination, 2023)

Atomic activation triggering selective photoreduction of CO2 to CH4 over NiAl-LDH/CeO2 heterojunction - Min Yang; Xingwang Zhu; Zi Zhu; Haiyan Zhang; Yuan Teng; Dai-Bin Kuang; Youji Li (Chemical Engineering Journal, 2023)

Acute and chronic effects of sublethal neonicotinoid thiacloprid to Asian honey bee (Apis cerana cerana) - Min Shi; Yi Guo; Yan-Yan Wu; Ping-Li Dai; Shao-Jun Dai; Qing-Yun Diao; Jing Gao (Pesticide Biochemistry and Physiology, 2023)

Third trimester as the susceptibility window for maternal PM2.5 exposure and preterm birth: A nationwide surveillance-based association study in China - Zhimei Qiu; Wenyan Li; Yang Qiu; Zhiyu Chen; Fumo Yang; Wenli Xu; Yuyang Gao; Zhen Liu; Qi Li; Min Jiang; Hanmin Liu; Yu Zhan; et al. (Science of The Total Environment, 2023)

Rheological property, β-carotene stability and 3D printing characteristic of whey protein isolate emulsion gels by adding different polysaccharides - Ming Li; Lei Feng; Yayuan Xu; Meimei Nie; Dajing Li; Cunshan Zhou; Zhuqing Dai; Zhongyuan Zhang; Min Zhang (Food Chemistry, 2023)

Duox mediated ROS production inhibited WSSV replication in Eriocheir sinensis under short-term nitrite stress - Rui Jia; Xiaoling Dai; Yanfang Li; Xintong Yang; Xiuwen Min; Derun Quan; Peng Liu; Xin Huang; Jiachun Ge; Qian Ren (Aquatic Toxicology, 2023)

Precisely modulate interfacial Bi-O bridge bond in Co-TCPP/Bi3O4Br to trigger long-lasting charge separation for boosting CO2 photoreduction - Yi Zhang; Fangyu Guo; Keke Wang; Jun Di; Bokki Min; Huiyuan Zhu; Hailong Chen; Yu-Xiang Weng; Jiayu Dai; Yuanbin She; Jiexiang Xia; Huaming Li (Chemical Engineering Journal, 2023)

Estimation the effect of accumulated long-range transported pollutants during a PM2.5 event in Taiwan - Hsin-Chih Lai; Yu-Tung Dai; Lan-Phuong Le; Bo-Han Pan; Li-Wei Lai; Min-Chuan Hsiao (Atmospheric Pollution Research, 2023)

Isochromenes from the Nicotiana tabacum -derived endophytic fungus Aspergillus versicolor and their anti-tobacco mosaic virus activities - Feng-Xian Yang; Jia-Meng Dai; Hua-Yin Liu; Qi-Li Mi; Jin Wang; Jian-Duo Zhang; Xue-Mei Li; Wei-Guang Wang; Min Zhou; Yin-Ke Li; Qiu-Fen Hu (Natural Product Research, 2023)

Juvenile hormone suppresses the FoxO-takeout axis to shorten longevity in male silkworm - Zhiquan Li; Jiangbo Song; Guihua Jiang; Yunzhu Shang; Yu Jiang; Jianfei Zhang; Li Xiao; Min Chen; Dongmei Tang; Xiaoling Tong; Fangyin Dai (Pesticide Biochemistry and Physiology, 2023)

Study on the relationship between lutein bioaccessibility and in vitro lipid digestion of nanostructured lipid carriers with different interface structures - Yayuan Xu; Xintian Li; Zhuqing Dai; Zhongyuan Zhang; Lei Feng; Meimei Nie; Chunquan Liu; Dajing Li; Min Zhang (Food Hydrocolloids, 2023)

Clonal fragmentation drives performance deterioration of epiphytic and lithophytic ferns in a karst forest - Qian Dai; Yu-Xuan Mo; Quan Chen; Liang Song; Li-Min Zhang; Gbadamassi G.O. Dossa; Hua-Zheng Lu (Flora, 2023)

Microbial species from multiple maternal body sites shape the developing giant panda ( Ailuropoda melanoleuca ) cub gut microbiome - Wei Guo; Ke Ren; Ruihong Ning; Caiwu Li; Yu Zhang; Yunong Gan; Xiaoyan Fu; Cenjun Xiao; Yaoyu Pang; Lei Cheng; Siyuan Zhang; Desheng Li; et al. (Molecular Ecology, 2023)
The gut microbiome of the giant panda ( Ailuropoda melanoleuca ) plays a vital role in nutrient acquisition from its specialized bamboo diet. Giant panda cubs harbour significantly different gut microbiota during their growth and development when feeding on milk before switching to bamboo. The fetal gut is sterile, and following birth, mother‐to‐infant microbial transmission has been implicated as a seeding source for the infant gut microbiota. Details of this transmission in giant pandas remain unclear. In this study, faecal samples were collected from seven panda mother–cub pairs when the cubs were 4–16 months old. Additional samples from the cubs' diet, soil and drinking water, and multiple body sites of the mothers were collected. Bacterial 16S rRNA gene sequencing and shotgun metagenomic sequencing were performed to determine the source and potential transmission routes of the cub gut microbiome. Source tracking analysis showed that maternal vagina, milk and faeces were the primary contributory sources of microbes, shaping the cub gut microbiome. Bacterial species from maternal faeces persisted the longest in the cub gut. Bacterial species in the diet contributed to the microbial community. Metagenomics analysis indicated that the predicted metabolic pathways of the gut microbiome also varied at different growth stages. Gut colonization with bacteria from various body sites of the mothers provides a foundational microbial community that is beneficial in fulfilling the evolving dietary needs of the cubs. This study suggests that mother‐to‐cub transmission is indispensable in shaping the gut microbiome of the developing panda cub.

Recovery of nickel from actual electroplating wastewater by integrated electrodeposition with adsorption pretreatment technique - Shuai Li; Min Dai; Imran Ali; Hengzhi Bian; Changsheng Peng (Process Safety and Environmental Protection, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Storms dominate the erosion of the Yangtze Delta and southward sediment transport - Shilun Yang; Tjeerd J. Bouma; Kehui Xu; Benwei Shi; Haifei Yang; Wenxiang Zhang; Xiangxin Luo; Peng Li; Yuanguang Huang; Min Tian; Leicheng Guo; Zhijun Dai (Science Bulletin, 2023)

Dynamics of a stochastic nutrient–plankton model with regime switching - Qing Guo; Yi Wang; Chuanjun Dai; Lijun Wang; He Liu; Jianbing Li; Pankaj Kumar Tiwari; Min Zhao (Ecological Modelling, 2023)

Sex difference on fibroblast growth factors (FGFs) expression in skin and wound of streptozotocin(STZ)-induced type 1 diabetic mice - Nuo-qi Wang; Wei-hua Jia; Lin Yin; Na Li; Mei-dai Liang; Jia-min Shang; Bi-yu Hou; Li Zhang; Gui-fen Qiang; Guan-hua Du; Xiu-ying Yang (Molecular Biology Reports, 2023)

A new phragmalin-type limonoid from the roots of Trichilia sinensis - Shou-Bai Liu; Jin-Ling Yang; Hui-Qin Chen; Cheng-min Yang; Hao Wang; Cai-Hong Cai; Jing-Zhe Yuan; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2023)

Description of a moderately acidotolerant and aerotolerant anaerobic bacterium Acidilutibacter cellobiosedens gen. nov., sp. nov. within the family Acidilutibacteraceae fam. nov., and proposal of Sporanaerobacteraceae fam. nov. and Tepidimicrobiaceae fam. nov. - Hui Fan; Jiang Li; Weidong Wu; Rui Chen; Min Yang; Yinggang Zhang; Lulu Cong; Lirong Dai; Yu Deng; Lei Cheng; Shichun Ma (Systematic and Applied Microbiology, 2023)

High-throughput virtual screening of metal–organic frameworks for xenon recovery from exhaled anesthetic gas mixture - Min Cheng; Shihui Wang; Zhiyuan Zhang; Li Zhou; Chong Liu; Yiyang Dai; Yagu Dang; Xu Ji (Chemical Engineering Journal, 2023)

Hominibacterium faecale gen. nov., sp. nov., an anaerobic l-arginine-degrading bacterium isolated from human feces - Noori Borhanudin; Min Yang; Andrei V. Chaplin; Jiang Li; Qiong Wang; Li-rong Dai; Ke-jia Wu; Shi-chun Ma; Boris A. Efimov; Lei Cheng (Archives of Microbiology, 2023)

Serum metabolic profiling of coal worker’s pneumoconiosis using untargeted lipidomics - Fangda Peng; Jing Dai; Qingjun Qian; Xiangfu Cao; Lifang Wang; Min Zhu; Shujin Han; Wubin Liu; Yan Li; Teng Xue; Xianyang Chen; Xiaoli Yang; et al. (Environmental Science and Pollution Research, 2022)

Indigenous PGPB Inoculant from Qinghai-Tibetan Plateau Soil Confer Drought-Stress Tolerance to Local Grass Poa annua - Yan Li; Min He; Yizhou Du; Xiupu Wang; Hui Zhang; Zhicong Dai; Justin S. H. Wan; Jiquan Sun; Congyan Wang; Daolin Du (International Journal of Environmental Research, 2022)

Competitiveness of alga Microcystis aeruginosa co-cultivated with cyanobacterium Raphidiopsis raciborskii confirms its dominating position - Zengling Ma; Xiaoqiao Zhang; Renhui Li; Min Wang; Wenli Qin; He Zhang; Gang Li; Henguo Yu; Chuanjun Dai; Min Zhao (Journal of Oceanology and Limnology, 2022)

Piperock ichnofabrics from western Henan, China: spatial distribution pattern and environmental controls on middle Cambrian carbonates - Bingchen Liu; Da Li; Min Wang; Mingyue Dai; Wenyi He; Jingbo Li; Yong’an Qi (International Journal of Earth Sciences, 2022)

Alternation of stromatolites and vertical burrows controlled by storm processes and sea-level changes in the middle Cambrian carbonates of central China - Bingchen Liu; Mingyue Dai; Yong’an Qi; Xiaofang Sun; Wei Zheng; Min Wang; Zhifeng Xing; Da Li; Yuchao Fan (Journal of Earth System Science, 2022)

Estimation of entity‐level land use and its application in urban sectoral land use footprint: A bottom‐up model with emerging geospatial data - Wei Xie; Huajun Yu; Yang Li; Min Dai; Xinyi Long; Nan Li; Yutao Wang (Journal of Industrial Ecology, 2022)
Land is an essential resource tomaintain the functioning of the socio‐economic system. Due to sectoral land data limitations, previous studies were primarily restricted to a coarse sectoral level or focused mainly on the global and national scales. However,fine‐scale land use data are required to provide tailored implications for municipal sustainable development. With emerging geographic data and novel methods, including point of interest data, road network data, and natural language processing, a bottom‐up model is developed to estimate the entity‐level artificial impervious land use. Then, we conducted a case study in Shanghai to investigate the spatial features, footprints, and intensities of sectoral land use. Our results indicated that 42 sectors in Shanghai had diverse spatial patterns. The transportation sector had the highest level of agglomeration among all sectors, and the manufacturing industry's adjacent land patches had higher sectoral heterogeneities than the service sector. The transportation sector had the largest direct and embodied land use footprint. The residential‐related sectors had higher land use intensities, while the high value‐added service sectors showed lower land use intensities. Our study indicates that this model offers a novel way of extracting entity‐level spatial land use information and is applicable for socio‐economic metabolism research. Future studies could incorporate remote sensing images and multiple databases to achieve higher resolution.

Harmful algal bloom-forming dinoflagellate Prorocentrum donghaiense inhibits the growth and photosynthesis of seaweed Sargassum fusiformis embryos - Caixia Wang; Min Wang; Binbin Chen; Wenli Qin; Lidong Lin; Chuanjun Dai; Hengguo Yu; Renhui Li; Min Zhao; Zengling Ma (Journal of Oceanology and Limnology, 2021)

Two new biflavanoids from Selaginella trichoclada Alsto - Yang Xie; Ping-Sheng Xu; Kang-Ping Xu; Zhen-Xing Zou; Gan Zhou; Dai Li; Dan Li; Xiao-Min Li; Jing Li; Gui-Shan Tan (Natural Product Research, 2021)

Microbiogenic thrombolites from the Cambrian Miaolingian Series of southern North China Craton - Xiaofang Sun; Mingyue Dai; Yong’an Qi; Bingchen Liu; Wei Zheng; Zhifeng Xing; Min Wang; Da Li; Yuchao Fan (Carbonates and Evaporites, 2021)

A new ent -kaurane diterpene from Isodon henryi - Xue Jiang; Ling-Xia Zhang; Qing-Mei Feng; Hong Wu; Ya-Lin Liu; De-Qin Wang; Li-Ping Dai; Zhi-Min Wang (Natural Product Research, 2021)

PPM1F in Dentate Gyrus Modulates Anxiety-Related Behaviors by Regulating BDNF Expression via AKT/JNK/p-H3S10 Pathway - Fantao Meng; Jing Liu; Juanjuan Dai; Haifeng Lian; Shujun Jiang; Qiongyu Li; Min Wu; Wentao Wang; Dan Wang; Di Zhao; Cuilan Liu; Changyun Qiu; et al. (Molecular Neurobiology, 2021)

Investigation of brain damage mechanism in middle cerebral artery occlusion/reperfusion rats based on i-TRAQ quantitative proteomics - Quantao Ma; Chunguo Wang; Min Wang; Yaqi Li; Pengfei Li; Jingkang Wang; Long Cheng; Yongcheng An; Hongyu Dai; Yuhui Duan; Ting Wang; Baosheng Zhao (Experimental Brain Research, 2021)

Sustained effects of one-time sewage sludge addition on rice yield and heavy metals accumulation in salt-affected mudflat soil - Wengang Zuo; Yanchao Bai; Ming Lv; Zehui Tang; Cheng Ding; Chuanhui Gu; Yuhua Shan; Qigen Dai; Min Li (Environmental Science and Pollution Research, 2021)

Ferruginous microbialite blooms of the Miaolingian (Cambrian) in the southern North China Craton: a response to the volcanic event? - Xiyang Zhang; Yong’an Qi; Yue Li; Mingyue Dai; Min Wang (Carbonates and Evaporites, 2020)

IL-33 deficiency protects mice from DSS-induced experimental colitis by suppressing ILC2 and Th17 cell responses - Xueying Qiu; Chang Qi; Xiaoxiao Li; Dai Fang; Min Fang (Inflammation Research, 2020)

Two new anthraquinone derivatives and one new triarylbenzophenone analog from Selaginella tamariscina - Rui Liu; Hui Zou; Zhen-Xing Zou; Fei Cheng; Xia Yu; Ping-Sheng Xu; Xiao-Min Li; Dai Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

The Potential Role of Marine Protein Hydrolyzates in Elevating Nutritive Values of Diets for Largemouth Bass, Micropterus salmoides - Min Dai; Songlin Li; Cefeng Fu; Hongjie Qiu; Naisong Chen (Frontiers in Marine Science, 2020)

Comparative genomics analysis of Nitriliruptoria reveals the genomic differences and salt adaptation strategies - Dai-Di Chen; Ye Tian; Jian-Yu Jiao; Xiao-Tong Zhang; Yong-Guang Zhang; Zhou-Yan Dong; Meng-Jie Xiong; Min Xiao; Wen-Sheng Shu; Wen-Jun Li (Extremophiles, 2020)

PEG-conjugated triacontanol micelles as docetaxel delivery systems for enhanced anti-cancer efficacy - Xiaoyu Lu; Min Fang; Yue Yang; Yu Dai; Jiaqiu Xu; Di Zhao; Yang Lu; Xijing Chen; Shan Lu; Ning Li (Drug Delivery and Translational Research, 2020)

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Interfacial Stress in the Development of Biologics: Fundamental Understanding, Current Practice, and Future Perspective - Jinjiang Li; Mary E. Krause; Xiaodong Chen; Yuan Cheng; Weiguo Dai; John J. Hill; Min Huang; Susan Jordan; Daniel LaCasse; Linda Narhi; Evgenyi Shalaev; Ian C. Shieh; et al. (The AAPS Journal, 2019)

Large Addition of Freshwater to the Tidal Reaches of the Yangtze (Changjiang) River - Xuefei Mei; Min Zhang; Zhijun Dai; Wen Wei; Weihua Li (Estuaries and Coasts, 2019)

Coupled effect of substrate and light on assimilation and oxidation of regenerated nitrogen in the euphotic ocean - Min Nina Xu; Xiaolin Li; Dalin Shi; Yao Zhang; Minhan Dai; Tao Huang; Patricia M. Glibert; Shuh‐Ji Kao (Limnology and Oceanography, 2019)
Nitrogen (N), as a critical element for microbial metabolisms, recycles rapidly in the euphotic ocean. Oxidation by nitrifiers is a competing pathway for phytoplankton assimilation of regenerated N (NH 4 + and urea). Sharing the overlapping substrates may result in competitive exclusion, thus, niche separation for the two assemblages. Both pathways are sensitive to light, but whether light intensity will intensify or alleviate such resource competition in the euphotic zone remains poorly explored in the field at the community level. By using 15 N labeling techniques, paired kinetic responses of uptake and oxidation were conducted in single bottles under manipulated light intensities for both NH 4 + and urea. We found light stimulated the maximum rate ( R m ) and specific affinities ( α U ) of both NH 4 + and urea uptake. In contrast, light effects were opposite for oxidation kinetics ( R m and α O ). As irradiance increased, the rapid increase in α U and concomitant decrease in α O imply a distinctive competition advantage of photosynthetic organisms over oxidizers under substrate‐limited environments. The ratio of α U / α O for NH 4 + ranged from 0.8 to 3089 (5.8–46,788 for urea) showing a distinct increasing pattern as ambient light increases, demonstrating that phytoplankton overwhelms nitrifiers throughout the oligotrophic euphotic zone, driving down concentrations and maintaining short turnover times of the two regenerated N substrates. Moreover, phytoplankton relied equally on NH 4 + and urea; yet, nitrifiers preferred NH 4 + to urea. In the nitrate‐depleted euphotic ocean, light acts as a crucial driver for utilization pathways of regenerated N and vertical niche separation.

Real-time precise orbit determination for BDS satellites using the square root information filter - Xiaolei Dai; Yidong Lou; Zhiqiang Dai; Yun Qing; Min Li; Chuang Shi (GPS Solutions, 2019)

Hsc70 Interacts with β4GalT5 to Regulate the Growth of Gliomas - Guan Sun; Ying Cao; Xueliang Dai; Min Li; Jun Guo (NeuroMolecular Medicine, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Genomic and transcriptomic insights into the survival of the subaerial cyanobacterium Nostoc flagelliforme in arid and exposed habitats - Jin‐Long Shang; Min Chen; Shengwei Hou; Tao Li; Yi‐Wen Yang; Qi Li; Hai‐Bo Jiang; Guo‐Zheng Dai; Zhong‐Chun Zhang; Wolfgang R. Hess; Bao‐Sheng Qiu (Environmental Microbiology, 2019)
Summary The cyanobacterium Nostoc flagelliforme is an extremophile that thrives under extraordinary desiccation and ultraviolet (UV) radiation conditions. To investigate its survival strategies, we performed whole‐genome sequencing of N. flagelliforme CCNUN1 and transcriptional profiling of its field populations upon rehydration in BG11 medium. The genome of N. flagelliforme is 10.23 Mb in size and contains 10 825 predicted protein‐encoding genes, making it one of the largest complete genomes of cyanobacteria reported to date. Comparative genomics analysis among 20 cyanobacterial strains revealed that genes related to DNA replication, recombination and repair had disproportionately high contributions to the genome expansion. The ability of N. flagelliforme to thrive under extreme abiotic stresses is supported by the acquisition of genes involved in the protection of photosynthetic apparatus, the formation of monounsaturated fatty acids, responses to UV radiation, and a peculiar role of ornithine metabolism. Transcriptome analysis revealed a distinct acclimation strategy to rehydration, including the strong constitutive expression of genes encoding photosystem I assembly factors and the involvement of post‐transcriptional control mechanisms of photosynthetic resuscitation. Our results provide insights into the adaptive mechanisms of subaerial cyanobacteria in their harsh habitats and have important implications to understand the evolutionary transition of cyanobacteria from aquatic environments to terrestrial ecosystems.

HDAC9 Polymorphisms Predict Susceptibility, Severity, and Short-Term Outcome of Large Artery Atherosclerotic Stroke in Chinese Population - Mengmeng Wang; Mengmeng Gu; Zibao Li; Bo Sun; Xi Cheng; Zhengze Dai; Shun Li; Lulu Xiao; Min Zhao; Zhaojun Wang; Ying Lin; Yahong Liu; et al. (Journal of Molecular Neuroscience, 2019)

Complete plastid genome of Bupleurum boissieuanum, an endemic herb plant in western China - Ying Wu; Tian-Ze Zhang; Dai-Yu Qiu; Qiang Chai; Wei-Bing Fan; Zhong-Hu Li; Min-Feng Fang (Conservation Genetics Resources, 2018)

Segmentation by domestic visitor motivation: Changbai Mountain Biosphere Reserve, China - Xiao-ping Gu; Bernard J. Lewis; Li-jun Niu; Da-pao Yu; Li Zhou; Wang-ming Zhou; Zhen-cai Gong; Zhi-juan Tai; Li-min Dai (Journal of Mountain Science, 2018)

Expression plasticity and evolutionary changes extensively shape the sugar‐mimic alkaloid adaptation of nondigestive glucosidase in lepidopteran mulberry‐specialist insects - Xiaotong Li; Liangen Shi; Xiangping Dai; Yajie Chen; Hongqing Xie; Min Feng; Yuyin Chen; Huabing Wang (Molecular Ecology, 2018)
During the co‐evolutionary arms race between plants and herbivores, insects evolved systematic adaptive plasticity to minimize the chemical defence effects of their host plants. Previous studies mainly focused on the expressional plasticity of enzymes in detoxification and digestion. However, the expressional response and adaptive evolution of other fundamental regulators against host phytochemicals are largely unknown. Glucosidase II ( GII ), which is composed of a catalytic GII α subunit and a regulatory GII β subunit, is an evolutionarily conserved enzyme that regulates glycoprotein folding. In this study, we found that GII α expression of the mulberry‐specialist insect was significantly induced by mulberry leaf extract, 1‐deoxynojirimycin (1‐ DNJ ), whereas GII β transcripts were not significantly changed. Moreover, positive selection was detected in GII α when the mulberry‐specialist insects diverged from the lepidopteran order, whereas GII β was mainly subjected to purifying selection, thus indicating an asymmetrically selective pressure of GII subunits. In addition, positively selected sites were enriched in the GII α of mulberry‐specialist insects and located around the 1‐ DNJ ‐binding sites and in the C‐terminal region, which could result in conformational changes that affect catalytic activity and substrate‐binding efficiency. These results show that expression plasticity and evolutionary changes extensively shape sugar‐mimic alkaloids adaptation of nondigestive glucosidase in lepidopteran mulberry‐specialist insects. Our study provides novel insights into a deep understanding of the sequestration and adaptation of phytophagous specialists to host defensive compounds.

The identification of IsiA proteins binding chlorophyll d in the cyanobacterium Acaryochloris marina - Zheng-Ke Li; Yan-Chao Yin; Lu-Dan Zhang; Zhong-Chun Zhang; Guo-Zheng Dai; Min Chen; Bao-Sheng Qiu (Photosynthesis Research, 2018)

Precise orbit determination of the Fengyun-3C satellite using onboard GPS and BDS observations - Min Li; Wenwen Li; Chuang Shi; Kecai Jiang; Xiang Guo; Xiaolei Dai; Xiangguang Meng; Zhongdong Yang; Guanglin Yang; Mi Liao (Journal of Geodesy, 2017)

New bisesquiterpenoid lactone from the wild rhizome of Atractylodes macrocephala Koidz grown in Qimen - Yunzhi Li; Min Dai; Daiyin Peng (Natural Product Research, 2017)

Construction and characterization of a bacterial artificial chromosome library for Camellia sinensis - Yuling Tai; Hao Wang; Chaoling Wei; Ling Su; Min Li; Liqun Wang; Zhaozhao Dai; Lingyun Shao; Jiayue Jiang; Meizhong Luo; Hua Yang; Weiwei Deng; et al. (Tree Genetics & Genomes, 2017)

Glycyrrhizin ameliorates experimental colitis through attenuating interleukin-17-producing T cell responses via regulating antigen-presenting cells - Xiangyu Chen; Dai Fang; Lingyun Li; Liyong Chen; Qirui Li; Feili Gong; Min Fang (Immunologic Research, 2017)

miR-143 regulates proliferation and differentiation of bovine skeletal muscle satellite cells by targeting IGFBP5 - Wei Ran Zhang; Hui Na Zhang; Yi Min Wang; Yang Dai; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2017)

Horizontal transfer of a novel Helentron in insects - Hua-Hao Zhang; Guo-Yin Li; Xiao-Min Xiong; Min-Jin Han; Fang-Yin Dai (Molecular Genetics and Genomics, 2017)

Citricoccus lacusdiani sp. nov., an actinobacterium promoting Microcystis growth with limited soluble phosphorus - Bing-Huo Zhang; Nimaichand Salam; Juan Cheng; Min Xiao; Han-Quan Li; Jian-Yuan Yang; Dai-Ming Zha; Wen-Jun Li (Antonie van Leeuwenhoek, 2016)

Implication of subsurface flow on rainfall-induced landslide: a case study - Wei Chao Li; F. C. Dai; Ying Qi Wei; Ming Long Wang; Hong Min; Lee Min Lee (Landslides, 2016)

Expression quantitative trait loci in long non-coding RNA PAX8-AS1 are associated with decreased risk of cervical cancer - Jing Han; Wen Zhou; Meiqun Jia; Juan Wen; Jie Jiang; Jufang Shi; Kai Zhang; Hongxia Ma; Jibin Liu; Jiansong Ren; Min Dai; Zhibin Hu; et al. (Molecular Genetics and Genomics, 2016)

Targeting AMPK signalling pathway with natural medicines for atherosclerosis therapy: an integration of in silico screening and in vitro assay - Tiantong Ou; Xumin Hou; Shaofeng Guan; Jinjie Dai; Wenzheng Han; Ruogu Li; Wenxia Wang; Xinkai Qu; Min Zhang (Natural Product Research, 2016)

Rhodiola rosea extends lifespan and improves stress tolerance in silkworm, Bombyx mori - Cong Chen; Jiangbo Song; Min Chen; Zhiquan Li; Xiaoling Tong; Hai Hu; Zhonghuai Xiang; Cheng Lu; Fangyin Dai (Biogerontology, 2016)

microRNA-128 regulates the proliferation and differentiation of bovine skeletal muscle satellite cells by repressing Sp1 - Yang Dai; Wei Ran Zhang; Yi Min Wang; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (Molecular and Cellular Biochemistry, 2016)

The role of microRNA-1 and microRNA-206 in the proliferation and differentiation of bovine skeletal muscle satellite cells - Yang Dai; Yi Min Wang; Wei Ran Zhang; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2016)

Identification and mapping stripe rust resistance gene YrLM168a using extreme individuals and recessive phenotype class in a complicate genetic background - Junyan Feng; Guoyue Chen; Yuming Wei; Yaxi Liu; Qiantao Jiang; Wei Li; Zhien Pu; Xiujin Lan; Shoufen Dai; Min Zhang; Youliang Zheng (Molecular Genetics and Genomics, 2015)

Travel motivation of domestic tourists to the Changbai Mountain Biosphere Reserve in Northeastern China: A comparative study - Xiao-ping Gu; Bernard J. Lewis; Yan-quan Li; Da-pao Yu; Li Zhou; Wang-ming Zhou; Sheng-nan Wu; Li-min Dai (Journal of Mountain Science, 2015)

Genome-wide identification and characterization of Fox genes in the silkworm, Bombyx mori - JiangBo Song; ZhiQuan Li; XiaoLing Tong; Cong Chen; Min Chen; Gang Meng; Peng Chen; ChunLin Li; YaQun Xin; TingTing Gai; FangYin Dai; Cheng Lu (Functional & Integrative Genomics, 2015)

Fine mapping of the qLOP2 and qPSR2-1 loci associated with chilling stress tolerance of wild rice seedlings - Ning Xiao; Wei-nan Huang; Ai-hong Li; Yong Gao; Yu-hong Li; Cun-hong Pan; Hongjuan Ji; Xiao-xiang Zhang; Yi Dai; Zheng-yuan Dai; Jian-min Chen (Theoretical and Applied Genetics, 2015)

Analysis on the Clinical Features of 507 HDV-Infected Patients - Xiao-hong Gu; Zhuo Chen; Ruo-yi Dai; Min-li Zhang; Hou-mei Tang; Lan-bo Chen; Bo Dong (Cell Biochemistry and Biophysics, 2014)

Characteristics of Malignant Tumors in 230 Husband–Wife Pairs - Ju Liu; Zhijian Xu; Kai Zhang; Huai Li; Sheng Chang; Xiaofeng Bi; Min Dai (Cell Biochemistry and Biophysics, 2014)

Ichnofabrics and their environmental interpretation from the fluvial deposits of the Middle Triassic Youfangzhuang Formation in Western Henan, Central China - Min Wang; Yongan Qi; Da Li; Mingyue Dai; Yuguang Chang (Journal of Earth Science, 2014)

The promoter and the 5′-untranslated region of rice metallothionein OsMT2b gene are capable of directing high-level gene expression in germinated rice embryos - Chung-Shen Wu; Dai-Yin Chen; Chung-Fu Chang; Min-Jeng Li; Kuei-Yu Hung; Liang-Jwu Chen; Peng-Wen Chen (Plant Cell Reports, 2014)

Functional identification of the gene encoding the enzyme involved in mannosylation in ramoplanin biosynthesis in Actinoplanes sp. - Jun-Sheng Chen; Yuan-Xi Wang; Lei Shao; Hai-Xue Pan; Ji-An Li; Hui-Min Lin; Xiao-Jing Dong; Dai-Jie Chen (Biotechnology Letters, 2013)

A birth cohort analysis of the incidence of ascending and descending colon cancer in the United States, 1973–2008 - Cairong Zhu; Bryan A. Bassig; David Zaridze; Peter Boyle; Min Dai; Qian Li; Tongzhang Zheng (Cancer Causes & Control, 2013)

A new phenylpropanoid from Peperomia tetraphylla - Yun-Zhi Li; Dai-Yin Peng; Min Dai; Cao-Mao Xiao; Hong-Bo Jiang; Jing Huang (Natural Product Research, 2013)

Dietary exposure to aluminium of urban residents from cities in South China - Qi Jiang; Jing Wang; Min Li; Xuxia Liang; Guangwei Dai; Zhikun Hu; Jian Wen; Qiong Huang; Yonghui Zhang (Food Additives & Contaminants: Part A, 2013)

Determination and depletion of amoxicillin residues in eggs - Kaizhou Xie; Min Zhao; Huisheng Guo; Xiaojie Zhang; Yingying Sun; Aihua Li; Xing Xie; Genxi Zhang; Guojun Dai; Jinyu Wang (Food Additives & Contaminants: Part A, 2013)

Subtype of dietary fat in relation to risk of Hodgkin lymphoma: a population-based case–control study in Connecticut and Massachusetts - Yongshun Gao; Qian Li; Bryan A. Bassig; Ellen T. Chang; Min Dai; Qin Qin; Yawei Zhang; Tongzhang Zheng (Cancer Causes & Control, 2013)

VSL#3 probiotics exerts the anti-inflammatory activity via PI3k/Akt and NF-κB pathway in rat model of DSS-induced colitis - Cong Dai; Chang-Qing Zheng; Fan-ji Meng; Zheng Zhou; Li-xuan Sang; Min Jiang (Molecular and Cellular Biochemistry, 2013)

Body size and risk of Hodgkin’s lymphoma by age and gender: a population-based case–control study in Connecticut and Massachusetts - Qian Li; Ellen T. Chang; Bryan A. Bassig; Min Dai; Qin Qin; Yongshun Gao; Yawei Zhang; Tongzhang Zheng (Cancer Causes & Control, 2013)

Neuroprotection by Silencing iNOS Expression in a 6-OHDA Model of Parkinson’s Disease - Min Li; Fu-rong Dai; Xiao-ping Du; Qi-dong Yang; Yuxiang Chen (Journal of Molecular Neuroscience, 2012)

Suppression of the root-knot nematode [Meloidogyne incognita (Kofoid & White) Chitwood] on tomato by dual inoculation with arbuscular mycorrhizal fungi and plant growth-promoting rhizobacteria - Runjin Liu; Mei Dai; Xia Wu; Min Li; Xingzhong Liu (Mycorrhiza, 2012)

Characterization of HbEREBP1, a wound-responsive transcription factor gene in laticifers of Hevea brasiliensis Muell. Arg. - Yue-Yi Chen; Li-Feng Wang; Long-Jun Dai; Shu-Guang Yang; Wei-Min Tian (Molecular Biology Reports, 2012)

High-level expression of bioactive recombinant human lysozyme in the milk of transgenic mice using a modified human lactoferrin BAC - Shen Liu; Xiangqing Li; Dan Lu; Shengzhe Shang; Meili Wang; Min Zheng; Ran Zhang; Bo Tang; Qiuyan Li; Yunping Dai; Ning Li (Transgenic Research, 2012)

A new QTL for resistance to Fusarium ear rot in maize - Zhi-Min Li; Jun-Qiang Ding; Rui-Xia Wang; Jia-Fa Chen; Xiao-Dong Sun; Wei Chen; Wei-Bin Song; Hua-Fang Dong; Xiao-Dong Dai; Zong-Liang Xia; Jian-Yu Wu (Journal of Applied Genetics, 2011)

Stability assessment of a slope under a transformer substation using numerical modelling - H. J. Li; F. C. Dai; W. C. Li; L. Xu; H. Min (Bulletin of Engineering Geology and the Environment, 2011)

Tissue-specific and expression of porcine growth hormone gene in BAC transgenic mice - Jia Tong; Simon G. Lillico; Ming Jun Bi; Tong Qing; Xiao Fang Liu; YuanYuan Wang; Min Zheng; Meili Wang; Yun Ping Dai; C. Bruce A. Whitelaw; Ning Li (Transgenic Research, 2011)

Combined administration of D-galactose and aluminium induces Alzheimerlike lesions in brain - Fei Xiao; Xiao-Guang Li; Xiao-Yu Zhang; Jun-Dai Hou; Lian-Feng Lin; Qin Gao; Huan-Min Luo (Neuroscience Bulletin, 2011)

The recombinant chimeric antibody chHAb18 against hepatocellular carcinoma can be produced in milk of transgenic mice - Jingjing Wei; Xiangmin Yang; Min Zheng; Meili Wang; Yunping Dai; Zhinan Chen; Ning Li (Transgenic Research, 2011)

Light at night and breast cancer risk: results from a population-based case–control study in Connecticut, USA - Qian Li; Tongzhang Zheng; Theodore R. Holford; Peter Boyle; Yawei Zhang; Min Dai (Cancer Causes & Control, 2010)

Dielectric barrier discharge plasma as a novel approach for improving 1,3-propanediol production in Klebsiella pneumoniae - Xiao-Yu Dong; Zhi-Long Xiu; Shuang Li; Ying-Min Hou; Dai-Jia Zhang; Chun-Sheng Ren (Biotechnology Letters, 2010)

Evaluation of recombinant endostatin in the treatment of atherosclerotic plaques and neovascularization in rabbits - Wei Mao; Jing Kong; Jin Dai; Zhao-quan Huang; Dong-zhi Wang; Gui-bao Ni; Min-li Chen (Journal of Zhejiang University-SCIENCE B, 2010)

Effects of sevoflurane preconditioning and postconditioning on rat myocardial stunning in ischemic reperfusion injury - An-lu Dai; Li-hua Fan; Feng-jiang Zhang; Mei-juan Yang; Jing Yu; Jun-kuan Wang; Tao Fang; Gang Chen; Li-na Yu; Min Yan (Journal of Zhejiang University-SCIENCE B, 2010)

Molecular cloning and sequence analysis of the sisomicin biosynthetic gene cluster from Micromonospora inyoensis - Wen-Rong Hong; Mei Ge; Zhi-Hong Zeng; Li Zhu; Min-Yu Luo; Lei Shao; Dai-Jie Chen (Biotechnology Letters, 2009)

Functional recombinant human anti-HAV antibody expressed in milk of transgenic mice - Ran Zhang; Man Rao; Chuan Li; Jingyuan Cao; Qinglin Meng; Min Zheng; Meili Wang; Yunping Dai; Mifang Liang; Ning Li (Transgenic Research, 2009)

Molecular cloning and sequence analysis of the sisomicin biosynthetic gene cluster from Micromonospora inyoensis - Wun-Rong Hong; Mei Ge; Zhi-Hong Zeng; Li Zhu; Min-Yu Luo; Lei Shao; Dai-Jie Chen (Biotechnology Letters, 2009)

High level expression of a functional human/mouse chimeric anti-CD20 monoclonal antibody in milk of transgenic mice - Bo Tang; Shanshan Yu; Min Zheng; Fangrong Ding; Rui Zhao; Jianmin Zhao; Yunping Dai; Ning Li (Transgenic Research, 2008)

A Male Reproduction-Related Kazal-Type Peptidase Inhibitor Gene in the Prawn, Macrobrachium rosenbergii: Molecular Characterization and Expression Patterns - Jun-Xia Cao; Jie-Qiong Dai; Zhong-Min Dai; Guo-Li Yin; Wei-Jun Yang (Marine Biotechnology, 2007)

Is Large Body Size always Advantageous for Terrestrial Adaptation? - Min-Li Tsai; Jan-Jung Li; Chang-Feng Dai (Evolutionary Ecology, 2000)

Why selection favors protandrous sex change for the parasitic isopod, Ichthyoxenus fushanensis (Isopoda: Cymothoidae) - Min-Li Tsai; Jan-Jung Li; Chang-Feng Dai (Evolutionary Ecology, 1999)